Serratus plane block: a novel ultrasound‐guided thoracic wall nerve block - Blanco, R.; Parras, T.; McDonnell, J. G.; Prats‐Galino, A. (Anaesthesia, 2013)
Summary We present a novel ultrasound‐guided regional anaesthetic technique that may achieve complete paraesthesia of the hemithorax. This technique may be a viable alternative to current regional anaesthetic techniques such as thoracic paravertebral and central neuraxial blockade, which can be technically more challenging and have a higher potential side‐effect profile. We performed the serratus block at two different levels in the midaxillary line on four female volunteers. We recorded the degree of paraesthesia obtained and performed fat‐suppression magnetic resonance imaging and three‐dimensional reconstructions of the spread of local anaesthetic in the serratus plane. All volunteers reported an effective block that provided long‐lasting paraesthesia (750–840 min). There were no side‐effects noted in this initial descriptive study. While these are preliminary findings, and must be confirmed in a clinical trial, they highlight the potential for the serratus plane block to provide analgesia following surgery on the thoracic wall. We suggest that this novel approach appears to be safe, effective, and easy to perform, and is associated with a low risk of side‐effects. This article is accompanied by an Editorial by Tighe and Karmakar, pp 1103–1106 of this issue.